2019
DOI: 10.1177/000313481908500846
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Realities of Delayed Splenic Bleeding

Abstract: Delayed splenic bleeding (DSB) is a poorly understood complication of blunt splenic injury. Treatment for splenic bleeding may involve splenectomy, but angioembolization is becoming a widely used adjuvant for management. Using the North Carolina Trauma Registry, this study aimed to evaluate the incidence, mortality, and risk factors for DSB in North Carolina. Using ICD-9 and ICD-10 codes, patients were stratified into two cohorts, those who underwent immediate splenectomy and those who were initially managed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Delayed diagnosis of bleeding episodes can be dangerous or even deadly. Peitzman et al reported 10 mortalities among 78 splenic injury patients with NOM failure 4 , 14 , 15 , 18 , and a 5–15% mortality rate have been reported by other studies 18 – 20 . Romeo et al reported two cases of delayed splenic bleeding presenting with haemorrhagic shock, who were then admitted for several months 21 .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Delayed diagnosis of bleeding episodes can be dangerous or even deadly. Peitzman et al reported 10 mortalities among 78 splenic injury patients with NOM failure 4 , 14 , 15 , 18 , and a 5–15% mortality rate have been reported by other studies 18 – 20 . Romeo et al reported two cases of delayed splenic bleeding presenting with haemorrhagic shock, who were then admitted for several months 21 .…”
Section: Discussionmentioning
confidence: 77%
“…Continuous monitoring is necessary, as the risk of bleeding remains even after discharge 2 . Therefore, identifying the signs and symptoms of bleeding after NOM is important for early detection, early haemostasis, and the prevention of unfavourable outcomes 14 , 15 . However, few studies have discussed the clinical manifestations of delayed splenic bleeding after NOM 14 16 .…”
Section: Introductionmentioning
confidence: 99%
“…It was rst described in 1902 by Baudet 33 , who noted its occurrence at 48 hours after trauma. Its incidence ranges from approximately 0.4-2% 10,34,35 and tends to occur between 4 and 8 days after injury 35 . Mortality ranges from 5-15%, compared with 1% mortality for acute injuries 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Adult patients aged > 18 years with splenic injury from 2000 to 2012 were included. Splenic injury was de ned based on the following International Classi cation of Diseases-Ninth Revision (ICD-9) diagnostic codes: 865.01 (hematoma of spleen without laceration) 10 , 865.02 (laceration without major disruption), 865.03 (laceration extending into the parenchyma), 865.04 (massive splenic parenchymal disruption), and 865.09 (unspeci ed splenic injury) 20,21 . Patients who died on the rst admission and underwent total splenectomy, partial splenectomy (ICD-9-OP codes 41.5, 41.42, 41.43 10 , and 41.95 20,21 ) or transcatheter arterial embolization (TAE) (ICD-9-OP codes 39.79 and 99.29) were excluded.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation